Effect of Performance Training on Biomechanical Indicators of Discus Throwing on Angled Surfaces and in Aquatic Environments - Saad Chellab; Essam Hassoon (Sinar Sport Journal, 2025)
This study investigates the impact of combined training using varied angled surfaces and aquatic environments on the biomechanical indicators of discus throwing performance in Iraqi youth athletes under 20 years old. The experimental design involved pre- and post-test assessments of key biomechanical parameters such as release speed, release angle, body rotation rate, and achieved distance. A purposive sample of 6 athletes, selected from 15, participated in a 10-week training program, which was implemented at the National Center for Talent Development in Baghdad, the Olympic Swimming Pool at Al-Sha'ab Sports Complex, and the Biomechanics Laboratory at the University of Baghdad. The training included a progressive increase in surface angle and water depth, targeting improved strength, coordination, and technical execution. Results showed significant improvements across all measured variables: release speed (15.48%), release angle (10.68%), body rotation rate (15.56%), and achieved distance (12.46%). Statistical analysis using paired t-tests indicated significant improvements (p < 0.001) in all biomechanical indicators. These findings suggest that the integrated approach of surface and aquatic training is effective in enhancing discus throwing performance, with implications for future training programs in track and field sports.